2022
DOI: 10.3390/ma15041392
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Preload Loss in Different Implant Abutment Connection Designs

Abstract: The stability and integrity of the abutment-implant connection, by means of a screw, is fallible from the moment the prosthetic elements are joined and is dependent on the applied preload, wear of the components and function. One of the main causes of screw loosening is the loss of preload. The loosening of the screw-abutment can cause complications such as screw fracture, marginal gap, peri-implantitis, bacterial microleakage, loosening of the crown and discomfort of the patient. It is also reported that loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The changes in preload with repeated screw tightening are not consistently described in the literature. Some authors have found an increase in preload with repeated tightening [ 4 , 15 , 22 ], others observed a decrease after retightening [ 18 , 23 25 ], and in some studies, the preload did not change [ 9 , 10 ]. These reports of differing preload changes after repeated tightening might be attributed to varying measuring methods, and especially the use of differing materials, which may have individual friction characteristics and wear phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in preload with repeated screw tightening are not consistently described in the literature. Some authors have found an increase in preload with repeated tightening [ 4 , 15 , 22 ], others observed a decrease after retightening [ 18 , 23 25 ], and in some studies, the preload did not change [ 9 , 10 ]. These reports of differing preload changes after repeated tightening might be attributed to varying measuring methods, and especially the use of differing materials, which may have individual friction characteristics and wear phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a higher risk of mechanical issues is reported in the literature, the screw-retained prosthesis is a reliable treatment and may have some biological advantages over the cement-retained prosthesis [ 18 , 19 , 20 , 21 , 22 , 23 ]. Although angulated SRCs can make it possible for dentists to use screw-retained crowns under the condition that only cement-retained crowns can be used, because of a lack of evidence and long-term clinical outcome data, dentists will be hesitant in using this unfamiliar component.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for loose screws is an insufficient preload. When the external load is beyond the preload, the abutment screw connection loses stability, affecting the vibration, and micromovement of the interfaces, which causes screw loosening [ 20 , 21 , 22 , 23 ]. An angulated SRC is usually used when the implant is in a suboptimal position; this may cause the implant abutment screw to receive larger lateral forces when functionally loaded, which may increase the chance of screw loosening.…”
Section: Discussionmentioning
confidence: 99%
“…This process occurs because the inside of the screw thread and the implant are not manufactured without irregularities and the micro-roughness of the metal is softened with the tightening force, causing a loss of 2%-10% of the initial torque. 12,13 For this reason, it is necessary to apply torque once more after 10 min to compensate for the effect of this loss. 22 Abutment screw loosening can, over time, result in screw fracture or even implant fracture if there is no prior intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In all groups, the torque was reapplied after 10 min to compensate the effects generated by the sedimentation phenomenon 12,13 …”
Section: Methodsmentioning
confidence: 99%